Dual RNA sequencing reveals dendritic cell reprogramming in response to typhoidal Salmonella invasion - Aulicino, A; Antanaviciute, A; Frost, J; Sousa Geros, A; Mellado, E; Attar, M; Jagielowicz, M; Hublitz, P; Sinz, J; Preciado-Llanes, L; Napolitani, G; Bowden, R; et al. (Springer Nature, 2022)
Salmonella enterica represent a major disease burden worldwide. S. enterica serovar Typhi (S. Typhi) is responsible for potentially life-threatening Typhoid fever affecting 10.9 million people annually. While non-typhoidal Salmonella (NTS) serovars usually trigger self-limiting diarrhoea, invasive NTS bacteraemia is a growing public health challenge. Dendritic cells (DCs) are key professional antigen presenting cells of the human immune system. The ability of pathogenic bacteria to subvert DC functions and prevent T cell recognition contributes to their survival and dissemination within the host. Here, we adapted dual RNA-sequencing to define how different Salmonella pathovariants remodel their gene expression in tandem with that of infected DCs. We find DCs harness iron handling pathways to defend against invading Salmonellas, which S. Typhi is able to circumvent by mounting a robust response to nitrosative stress. In parallel, we uncover the alternative strategies invasive NTS employ to impair DC functions.